2017
DOI: 10.1111/lcrp.12104
|View full text |Cite
|
Sign up to set email alerts
|

Interviewers’ approaches to questioning vulnerable child witnesses: The influences of developmental level versus intellectual disability status

Abstract: Purpose Children with intellectual disabilities (CWIDs) are vulnerable to victimization, but we know little about how to interview them about possible maltreatment. We examined whether interviewers used proportionally more direct and option‐posing, and fewer open questions, with CWID than with typically developing (TD) children or with less mature children regardless of disability, taking into account the contribution of the amount of information conveyed by the child. Method One hundred and twelve children (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 83 publications
(117 reference statements)
1
22
0
2
Order By: Relevance
“…The quality of the interview techniques used in investigative interviews of PWID and PWA is therefore frequently referred to as a challenge in discussions of witness credibility. Additionally, studies have shown a relationship between the question types used and the accuracy of the witness account, for both PWID (Agnew and Powell 2004;Ternes and Yuille 2008;Gudjonsson and Joyce 2011;Brown and Lamb 2015;Brown et al 2017;Lamb et al 2018b;Morrison et al 2019) and PWA (Maras and Bowler 2014;Almeida et al 2018). The majority of these studies have, however, been conducted with children with or without ID in experimental settings (e.g.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The quality of the interview techniques used in investigative interviews of PWID and PWA is therefore frequently referred to as a challenge in discussions of witness credibility. Additionally, studies have shown a relationship between the question types used and the accuracy of the witness account, for both PWID (Agnew and Powell 2004;Ternes and Yuille 2008;Gudjonsson and Joyce 2011;Brown and Lamb 2015;Brown et al 2017;Lamb et al 2018b;Morrison et al 2019) and PWA (Maras and Bowler 2014;Almeida et al 2018). The majority of these studies have, however, been conducted with children with or without ID in experimental settings (e.g.…”
mentioning
confidence: 99%
“…The majority of these studies have, however, been conducted with children with or without ID in experimental settings (e.g. watching staged events or videos followed by an interview) (Agnew and Powell 2004;Brown et al 2017;Almeida et al 2018;Lamb et al 2018b). Some studies have examined interviews of adults with ID and autism in an experimental setting.…”
mentioning
confidence: 99%
See 3 more Smart Citations